Contribution to the knowledge of the biocoenosis of Myzus varians Dav. (Bollettino di zoologia agraria e bachicoltura, 2024)
Myzus varians Dav. showed abundant populations in ecosystems and agro-ecosystems in which both the primary host, Prunus persica (L.), and the secondary one, Clematis spp., are present. In such environments it appeared inserted in a very rich biocoenosis in which 6 species of limiters (31 predators and 12 parasites), of which 35 not yet reported for this aphid, were found. Among the limiters, 27 species on peach, 4 on clematis, and 12 on both the vegetable hosts were encountered. The predators include: 1 Trombidiidae, 1 Gryllidae, l Miridae, 1 Anthocoridae, 2 Nabidae, 2 Hemerobiidae,4 Chrysopidae, 1 Cecidomyiidae, 6 Syrphidae, 1 Staphilinidae, 1 Cantharidae, 10 Coccinellidae. The parasites are represented by 7 Aphidiidae, 1 Zygomycete, 1 Blastomycete, 3 Hyphomycetes. The trophobionts are Formicidae. The rapid adaptation of many autochthonous species to M. varians, an aphid recently introduced into Europe, demonstrated the capability of the organisms to establish new and complex biocoenoses in a quick way.
Keywords: peach; aphids; predators; parasites; fungi